Characterization and analysis of fluoride calcium silicate composite interface in remineralization of dental enamel. (15th November 2018) - Dong, Zhihong; Ni, Yanting; Yang, Xiangjun; Hu, Cheng; Sun, Jianxun; Li, Lei; Zhou, Changchun; Fan, Hongyuan
Abstract: Tooth enamel is easily demineralization due to all kinds of food or drinking attacking, and fluoride calcium silicate (FCaSiO4 ) is widely used in demineralized enamel repair due to its good biocompatibility and bioactivity. In this study, FCaSiO4 as remineralized enamel reagent was used to repair acidic enamel by simulated tooth brushing. The surface morphology of FCaSiO4 was observed by scanning electron microscope (SEM) and atomic force microscope (AFM). Altrathin section samples were prepared by Dual-beam focused ion-beam (FIB) system for further observing the interface structure and crystalline by high resolution transmission electron microscopy (HRTEM) selected-area electron diffraction (SAED). Composition was evaluated by energy dispersion X-ray spectroscopy (EDX). The results indicated that FCaSiO4 can rapidly induce apatite formation for 24 h in human saliva and the mineralized layer's thickness was at 200–370 nm, and interface between mineralized layer and enamel matrix bonded well. This study indicated that FCaSiO4 may be a promising toothpaste additives/dentifrices as demineralized enamel restoration.